The Economics of electricity markets theory and policy - Ranci, Pippo; Cervigni, Guido (Cheltenham, UK Edward Elgar, 2013)
The Economics of Electricity Markets provides a cutting-edge analysis of the critical issues involved in the design and operation of electricity markets, as well as an assessment of alternative institutional arrangements that have either been implemented or are under discussion in Europe and the US. The book illustrates how a sound market design can render electricity trading and retailing very much like that of other commodities. Social and political concerns, rather than engineering or economics, are what make electricity markets 'special'. The expert contributors address a wide set of issue.
Introduction / Pippo Ranci and Guido Cervigni -- Wholesale electricity markets / Guido Cervigni and Dmitri Perekhodtsev -- Generation capacity adequacy / Guido Cervigni, Andrea Commisso and Dmitri Perekhodtsev -- Congestion management and transmission rights / Dmitri Perekhodtsev and Guido Cervigni -- Competition policy in the electric industry / Guido Cervigni and Dmitri Perekhodtsev -- Retail competition / Anna Creti and Clara Poletti -- Climate change and the future of the liberalised electricity markets / Guido Cervigni.
Keywords: Electric utilities